Evaluating the adaptive reuse potential of buildings in conservation areas. Issue 3 (7th March 2017) - Hong, Yan; Chen, Fei
Abstract : Purpose: Adaptive reuse of building assets is an important approach to sustainability. Adapting a building for new uses often involves complex factors in the decision-making process, particularly in conservation areas. The paper aims to show an evaluation process of the adaptive reuse potential of historic buildings that are subject to change in the Grand Canal area, a world heritage site in Hangzhou, China. Design/methodology/approach: For this purpose, a model has been established with aggregated views of professionals on the degree to which a variety of factors affect the buildings' potential for adaptive reuse. The model intends to help prioritise some of the buildings in the area for adaptive reuse, which is important for effective allocation of public resources. Interviews with professionals, analytic hierarchy process and the Delphi method have been used to establish the evaluation model. It is then applied to the Grand Canal area to generate indices for buildings' adaptive reuse potential and the ranking of priority. The indices are generated through public scoring of historic buildings against the variables and calculated through the model. Findings: The paper concludes that the evaluation process is an effective way to engage the public in the decision-making process and to balance conflict interests of various stakeholders in the management of historic building assets in conservation areas. Originality/value: The research has proposed an evaluation model to help set priority of buildings subject to adaptive reuse and to help distribute public fund effectively. It facilitates wide public engagement in the decision-making progress of adaptive reuse of historic buildings.